Avenues for sport-related concussion prevention in high school football: effect of limiting collision practices - Bretzin, A. C.; Tomczyk, C. P.; Wiebe, D. J.; Covassin, T. (Journal of Athletic Training, 2022)
Context Football continues to demonstrate the highest rate of sport-related concussion (SRC) in high school athletics. To mitigate the SRC risk, the Michigan High School Athletic Association (MHSAA) implemented rules aimed at reducing the number of collisions occurring in practices.